Radical Scavenging Capacity and Antioxidant Activity of the Vitamin E Extracted from Palm Fatty Acid Distillate by Sequential Cooling Hexane - Ronnakorn Sroynak; Pramoun Srikalong; Patcharin Raviyan (My University, 2013)
The radical scavenging capacity and antioxidant activity of the vitamin E extracted from palm fatty acid distillate by the sequential cooling hexane were compared to those of the synthetic antioxidants including butylated hydroxyanisole (BHA), 2,6-di-tert-butyl-4-methylphenol (BHT), pyrogallol (PG), tert-butylhydroquinone (TBHQ) and commercial Alpha-tocopherol. The extracted vitamin E contained 2,509.57, 9.24, 157.85, 6.70, 1,779.92, 3.97, 2,376.38, 818.80 and 7,662.45 ppm of Alpha-, Beta-, Gamma-, Delta-tocopherol and Alpha-, Beta-, Gamma-, Delta-tocotrienol, and total vitamin E, respectively. The maximum 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity of 20 ppm extracted vitamin E was 89%. The antioxidant activity determined by the methods of reducing power and ferric thiocyanate indicated that the 2.5 ppm extracted vitamin E could inhibit the oxidation of linoleic acid emulsion for more than 80% within 1 day. The superoxide scavenging activity of the extracted vitamin E was greater than those of the BHT, commercial Alpha-tocopherol, and PG, respectively. The antioxidant activity of the extracted vitamin E was 91% which was similar to those of the BHT and synthetic Alpha-tocopherol. The total-vitamin E remained 73% after heating at 190°C for 3 h. The tocopherol derivatives were more heat-stable than the tocotrienol derivatives while Gamma-tocopherol was the most heat-stable derivative. The concentration of total-vitamin E stored at 30°C for 120 days remained about 87% while the concentrations of vitamin E derivatives reduced by 2-20%.
Keywords: Butylated hydroxyanisole; Butylated hydroxytoluene; Free Radicals and Antioxidants